A Case Report: Effects of a ketogenic diet on PTEN mutation-associated autism spectrum disorder - Wang, Yu; Guo, Yanshuo; Zhu, Mengna; Zhang, Linlin; Wang, Lihong; Liu, Zhiyue; Zhao, Yongheng; Yan, Zihan; Gao, Jiayi; Cao, Aihua (Frontiers in Nutrition, 2026)
BackgroundAutism spectrum disorder (ASD), a neurodevelopmental condition strongly associated with PTEN mutations, demonstrates limited responsiveness to current therapeutic approaches. Ketogenic diet (KD) has emerged as a promising dietary intervention in neurological disorders, including epilepsy and ASD.ObjectiveThis case report investigates the clinical efficacy and potential mechanisms of KD in an ASD patient with a PTEN mutation, providing evidence for genetics-guided precision nutrition therapy.MethodsWe present a 7-year, 1-month-old male with ASD and a pathogenic heterozygous PTEN p. Arg130Gln mutation, who showed suboptimal response to conventional treatments. He received a modified Atkins diet (60% fat, 30% protein, 10% carbohydrates) for 1 month, followed by 5 months of combined KD and repetitive transcranial magnetic stimulation (rTMS). Efficacy was evaluated through serial behavioral assessments, metabolic markers (blood ketones, inflammatory cytokines), and EEG monitoring. Safety parameters were documented.ResultsDuring the intervention, mean blood glucose was 4.4 mmol/L and ketones averaged 2.4 mmol/L. Significant improvements in behavior, sleep, and metabolic profiles were observed. Parents noted symptomatic improvement by day 6. Quantitative assessments (behavioral scales, metabolic markers, EEG) confirmed substantial progress after 1 month of KD and 5 months of KD-rTMS versus baseline. While the rate of improvement diminished during combined therapy compared to initial KD monotherapy, excitatory behaviors (e.g., screaming, uncontrolled running, sleep-onset difficulties) were markedly reduced compared to prior rTMS-only treatment. No adverse events (e.g., hypoglycemia, ketoacidosis) occurred, and the regimen was well-tolerated.ConclusionThis study provides preliminary clinical evidence for KD in PTEN-related ASD, suggesting potential modulation of the PI3K/AKT/mTOR pathway and neuroinflammation. Although limited by its single-case design and short duration, it offers a novel therapeutic approach for PTEN-mutant ASD. Multicenter randomized controlled trials are warranted to validate efficacy and safety.